Elevated remnant cholesterol and non-HDL cholesterol concentrations from real-world laboratory results: a cross-sectional study in Southeast Asians - Loh, Wann Jia; Soh, Heng Samuel; Tun, Mon Hnin; Tan, Pei Ting; Lau, Chin Shern; Tavintharan, Subramaniam; Watts, Gerald F.; Aw, Tar Choon (Frontiers in Cardiovascular Medicine, 2024)
Introduction Triglyceride-rich remnant lipoproteins (TRLs) are considered atherogenic due to the presence of remnant cholesterol, which is transported by apolipoprotein B. In clinical practice, the concentration of TRLs can be estimated by calculating remnant cholesterol or non-HDL cholesterol levels. Aim This study aims to investigate the proportion of patients who have low LDL cholesterol (LDL-C) concentration but elevated remnant cholesterol concentration, stratified by the presence of hypertriglyceridaemia and ethnicity, using real-world hospital data. Our secondary aim is to investigate the proportion of patients with elevated non-HDL cholesterol levels using guideline-recommended goals. Methods A 2-year retrospective study was conducted at a single centre, analyzing lipid blood tests of all patients, including directly measured LDL-C. Fasting for blood tests was not mandatory. Results The study included a total of 21,605 consecutive patients with plasma lipid profiles analyzed in our hospital laboratory. The median age was 61 years. In patients with ASCVD (n = 14,704), 23.7% had an LDL-C level of <1.8 mmol/L, 11.3% had elevated remnant cholesterol concentrations at ≥0.65 mmol/L, and 48.8% were at the non-high-density lipoprotein cholesterol (non-HDL-C) goal (<2.6 mmol/L). Among patients diagnosed with atherosclerotic cardiovascular disease (ASCVD) with LDL-C levels of <1.8 mmol/L (n = 3,484), only 11.9% had high levels of remnant cholesterol, but 96% of the ASCVD patients also achieved the recommended non-HDL-C target of <2.6 mmol/L. When the LDL-C level was <1.8 mmol/L, the mean concentration of remnant cholesterol was 0.214 mmol/L when the triglyceride level was <1.7 mmol/L (n = 3,380), vs. 0.70 mmol/L when the triglyceride level was elevated (n = 724), p < 0.001. Among patients with a triglyceride level of ≥1.7 mmol/L and an LDL-C level of <.8 mmol/L, there were 254 patients with elevated remnant cholesterol concentration and 71 patients with suboptimal non-HDL levels. Malays had a higher mean remnant cholesterol concentration compared with both Chinese and Indians across all LDL-C levels, particularly in the presence of hypertriglyceridaemia. Conclusions An elevated remnant cholesterol concentration of >0.65 mmol/L was present in 11% of all patients. The current guideline-recommended non-HDL-C goal, which uses a 0.8 mmol/L estimate of remnant cholesterol concentration, was achieved in >92% of patients, suggesting that it is unlikely to be clinically useful for the majority of our patient population except where there is concomitant hypertriglyceridaemia. Further studies are needed to establish the appropriate non-HDL-C goal or calculated remnant cholesterol concentration, paired with the LDL-C goal or otherwise, in a Southeast Asian population.